Hydrodeoxygenation of anisole to produce value-added products: ortho-, meta-, para-cresol - Guerrero Zúñiga, Leonor Angélica; Ramirez-Gallardo, Ana Cristina; López Sánchez, Maria Fernanda; Garcia-Cruz, Isidoro (Renewable Energy, Biomass & Sustainability, 2025)
This work presents a detailed study on the trans-methylation reaction using density functional theory (DFT), an advanced computational technique for analyzing and predicting molecular-level interactions. Trans-methylation is a crucial step in both catalytic and non-catalytic decomposition of methoxybenzene (anisole), with a special focus on processes generating free radicals and methyl-type carbocations through the cleavage of the methyl group. The study highlights that, in the presence of Brønsted-acid catalysts (such as HZSM-5), trans-methylation follows a specific mechanism involving dual electrophilic attack. This process begins with the interaction of the Brønsted acid proton with the oxygen atom in anisole, leading to carbocation substitution. This dual electrophilic attack mechanism is key as it explains how the catalyst alters reaction pathways to improve efficiency. Computational modeling of the reaction shows that the use of acidic catalysts drastically lowers the energy barriers of the investigated compounds, indicating that Brønsted acidity facilitates the reaction. In many cases, the reduction exceeds 40 kcal/mol, with the most significant decrease observed for ortho-cresol, where the energy barrier drops by approximately 60 kcal/mol. This demonstrates the significant influence of the catalyst on reaction kinetics. Both in catalytic and non-catalytic trans-methylation, there is a clear structural preference for the anisole molecule and its derivatives, such as cresols. The ortho and para positions are the most favored for substitution, especially when the substituents are oxygen-rich. This is because oxygenated substituents tend to lower energy barriers and enhance the reactivity of the aromatic ring, as seen in the decomposition of anisole into phenolic derivatives. This work demonstrates how the use of Brønsted-acid catalysts not only accelerates trans-methylation reactions but also alters the preferred reaction pathways, significantly reducing energy barriers. This opens the door to a deeper understanding and optimization of industrial processes involving the decomposition of aromatic compounds such as anisole. The production of benzene, toluene, and xylene (BTX), along with oxygenated aromatic compounds such as anisole and cresol, plays a significant role in various industrial applications, including the synthesis of polymers, resins, and fuel additives. While the manufacture of these aromatics is associated with environmental concerns—particularly emissions and toxic by-products—their contribution to sustainability can be enhanced through the adoption of greener synthesis pathways, improved catalytic efficiency, and the integration of renewable feedstocks. When aligned with circular economy principles and process intensification strategies, the production of BTX and oxygenated aromatics can support more sustainable chemical manufacturing frameworks.